Accelerometer-measured daily step counts and adiposity indicators among Latin American adults : a multi-country study - Ferrari, Gerson (2021)
© 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).